Genetic and agronomic characterization of chickpea landraces for resistance to Fusarium oxysporum f. sp. ciceris - Fierro, Marco; Palmieri, Davide; De Curtis, Filippo; Vitullo, Domenico; Rubio, Josefa; Gil, Juan; Lima, Giuseppe; Millan, Teresa (Phytopathologia Mediterranea, 2019)
Chickpea, with annual grain production of approx. 15 million tons, is the third largest world pulse crop, which is an important source of protein for human and animal diets. In Italy, chickpea production is mainly based on landraces cultivated on small farms. However, the attention that consumers give to local products stimulates farmers to extend the use of chickpea landraces by reintroducing them in crop rotations. Production of chickpea using landraces can be adversely affected by agronomic factors and, particularly, plant diseases such as Fusarium wilt, caused by the widespread fungal pathogen Fusarium oxysporum f. sp. ciceris (Foc). Therefore, studies of agronomic adaptation of landraces and on disease resistance are needed. The most important agronomic traits and levels of resistance to Foc were evaluated for 18 chickpea landraces collected from Central Italy. These landraces were also characterized for their genetic traits in comparison to some of the main Spanish cultivars, and to two reference cultivars with worldwide distribution. Molecular characterization showed variability in genetic and phenotypic traits among the Italian landraces. In particular, landrace 203 locally known as “Longano” was resistant to Foc and could be considered in chickpea breeding programmes. Comparative analyses based on molecular markers showed, with some exceptions, that the Italian landraces are genetically different compared to the main Spanish cultivars analyzed in this study.